(untitled) (ZARCH, 2021)
Jedediah Purdy After Nature: A Politics of the Anthropocene Cambridge, Massachusetts: Harvard University Press, 2015. 336 p. Idioma: inglés. Tapa dura. 31,50 € ISBN: 9780674368224